High Pretreatment LDH Predicts Poor Prognosis in Hypopharyngeal Cancer - Wu, Jialing; You, Kaiyun; Chen, Changlong; Zhong, Huimin; Jiang, Yanhui; Mo, Huaqian; Song, Juanjuan; Qiu, Xingsheng; Liu, Yimin (Frontiers in Oncology, 2021)
Background: Elevated pretreatment lactate dehydrogenase(LDH) has been associated with poor prognosis in various malignancies, however, its prognostic role in hypopharyngeal cancer remains elusive. In this study, we aimed to assess the association between pretreatment LDH and clinical outcome of hypopharyngeal cancer. Methods: We retrospectively collected 198 hypopharyngeal cancer patients treated with surgery in our institution between 2004 and 2018. The prognostic role of pretreatment LDH was explored by using univariate and multivariate analysis. Besides, subgroup analysis was performed based on T stage. Results: Three-year and Five-year of disease-free survival (DFS, 67.0% vs. 57.4%, 65.8% vs. 39.8%, p=0.007 ) and overall survival (OS, 74.8% vs. 68.9%, 66.8% vs. 50.8%, p=0.006) exhibited significant differences between low LDH level and high LDH level groups. Univariate analysis showed that, pretreatment elevated serum LDH served as an unfavorable determinant with regard to DFS and OS. Further multivariate analysis also confirmed that LDH was independent predictor for DFS and OS. Additionally, N status and age were also found to be significantly associated with both DFS and OS. Conclusion: Pretreatment elevated serum LDH is an inferior prognostic factor for patients with hypopharyngeal cancer. These results should be validated by more multicenter and prospective studies.